Dental stem cell sphere formation and potential for neural regeneration: A scoping review - Mohammed S. Basabrain; Ahmed Zaeneldin; Mohammed Nadeem Bijle; Chengfei Zhang (Heliyon, 2024)
Background: Dental stem cells with neurosphere-forming abilities are a promising cell source for the treatment of neural diseases and injuries. This scoping review aimed to systematically map the existing literature on dental sphere formation assays and their characteristics associated with neural regeneration potential. Methods: The Web of Science, EMBASE, SCOPUS, and PubMed databases were systematically searched for in vitro, animal, and clinical studies and reviews focusing on stem cells isolated from the oral cavity, subsequently cultured as spheres with neural regeneration potential. Data were extracted and evidence was synthesized according to the predetermined variables in the registered protocol. Results: A total of 35 articles (31 in vitro, 1 combined in vitro and in vivo, and 3 reviews) were included. The predominant method utilized for sphere formation was low-attachment culture. Spheres were characterized using assessment of neural marker expression via confocal microscopy, immunohistochemistry, RT-qPCR, or western blotting. Overall, the synthesized results indicate a lack of in vivo studies investigating the utility of dental neurospheres for neural regeneration, with dental pulp stem cells being the most investigated for their neural regenerative potential. Conclusion: Dental stem cell spheres demonstrate significant potential for neural regeneration. Several assays and characterizations have been performed to characterized the mechanisms underlying dental sphere formation. Furthermore, in vivo studies are imperative to deduce the neural regenerative potential of stem cells in complex biological environments.